P. Masiotas in education mathematics equations in periodical journal „Švietimo darbas“ - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2014)
P. Masiotas teaching mathematics equation in periodical journal „Švietimo darbas“ between the two word wars are introduced in article. These articles provide unconventional solutions to the equation.